FEATURES OF WORDS USED IN RESTAURANT MENUS: A Sociopragmatic Perspective - Setya Budiasningrum, Retno; Suhardianto, Suhardianto; Setiawan, Jajang; Satri Efendi, Ali (Jurnal Konseling Pendidikan Islam, 2023)
The culinary business has been growing so fast and competitively that it needs specific ways to attract customers. The food names, one thing people can directly see in restaurants or cafes, should be attractive and persuasive as they can be used as an indirect advertisement. This research aims at tracing the features of words used in naming foods for restaurant menus and how they fulfill the function of informing, attracting, and persuading customers. This study used a qualitative method to explore the naming of food on the menus of fifty restaurants in Malang, East Java, Indonesia. The finding showed the words related to the element of the ingredient were mostly found in the naming of dishes on the menus. There were food names consisting of only one feature of the word, such as Krengsengan, Lodeh, and Mendol, which were the traditional food names; however, there were also names that used a combination of those features.